A reincidência da gravidez na adolescência e a evasão escolar - Avila, Iris Teresa Lafuente [UNESP] (2015)
It is estimated that in Brazil since 2000, each year, one million adolescents between ten and twenty years old, give birth. The probability of occurring a new teenage pregnancy is high, more frequent in no single stable mate. The vast majority of pregnant adolescents have low education and school dropout. This study analyzes the general recurrence of teen pregnancy by checking the possible reasons contributing to truancy seeking for possible ways to contribute to the reintegration of teenage mothers in school. The approach adopted for this study was the analysis of documents. The study included four teenagers, female, treated by the Psychology of Public Service of a municipal maternity of Araraquara - SP / Brazil, in 2012. They became pregnant more than once, and were in the age group fourteen to nineteen, having in common the fact that they left school. The analyzed material was composed of the socioeconomic questionnaire and the analysis of a documentary journal, produced by adolescents. The analysis included themes of documentary diary: childhood, adolescence, motherhood, first pregnancy, school life, the school after the first pregnancy, the school from the second pregnancy, the return to school, professional and labor expectations, family and resources social and educational support. Among the main results, we highlight the psychosocial and educational consequences of teenage pregnancy and the recurrence of pregnancy. We emphasize the importance of support networks (family and school) to help teenage mothers. Schools do not develop prevention programs, sex education, and intervention programs to accommodate teenage mothers, and so avoid truancy. The study suggests intervention programs allied with the Departments of Health and Education, to develop sex education of adolescents